On the weak localization principle of the eigenfunction expansions of the laplace-beltrami operator by Riesz Method - Anvarjon Ahmedov; Ahmad Fadly Nurullah Rasedee (Universiti Putra Malaysia, 2024)
In this paper we deal with the problems of the weak localization of the eigenfunction expansions related to Laplace-Beltrami operator on unit sphere. The conditions for weak localization of Fourier-Laplace series are investigated by comparing the Riesz and Cesaro methods of summation for eigenfunction expansions of the Laplace- Beltrami operator. It is shown that the weak localization principle for the integrable functions f (x) at the point x depends not only on behavior of the function around x but on the behavior of the function around diametrically opposite point x.